75.7k views
3 votes
BRIANLIEST HELP!!!

Find the error & explain why it is wrong:
(3x^2y^4)^2 = 6x^4y^8

BRIANLIEST HELP!!! Find the error & explain why it is wrong: (3x^2y^4)^2 = 6x-example-1

1 Answer

6 votes

Answer:

Explanation:

Given expression is (3x²y⁴)²

We can rewrite the given expression as,

(3x²y⁴)² = (3)²(x²)²(y⁴)² [Every term of the the expression will be squared]

= 9x⁴y⁸

But in the picture attached, it has been given as (6x⁴y⁸).

Therefore, in place of 6 it should be 9.

User Hardik Patel
by
5.5k points